Plasma-polymerized hexamethyldisilazane treated by nitrogen plasma immersion ion implantation technique - Honda, Roberto Yzumi [UNESP]; Mota, Rogério Pinto [UNESP]; Batocki, R. G. S. [UNESP]; Santos, D. C. R. [UNESP]; Nicoleti, T. [UNESP]; Kostov, K. G. [UNESP]; Kayama, M. E. [UNESP]; Algatti, M. A. [UNESP]; Cruz, N. C.; Ruggiero, L. (Iop Publishing Ltd, 2009)
This paper describes the effect of nitrogen Plasma Immersion Ion Implantation (PIII) on chemical structure, refraction index and surface hardness of plasma-polymerized hexamethyldisilazane (PPHMDSN) thin films. Firstly, polymeric films were deposited at 13.56 MHz radiofrequency (RF) Plasma Enhanced Chemical Vapour Deposition (PECVD) and then, were treated by nitrogen PIII from 15 to 60 min. Fourier Transformed Infrared (FTIR) spectroscopy was employed to analyse the molecular structure of the samples, and it revealed that vibrations modes at 3350 cm(-1), 2960 cm(-1), 1650 cm(-1), 1250 cm(-1) and 1050 cm(-1) were altered by nitrogen PIII. Visible-ultraviolet (vis-UV) spectroscopy was used to evaluate film refractive index and the results showed a slight increase from 1.6 to 1.8 following the implantation time. Nanoindentation revealed a surface hardness rise from 0.5 to 2.3 GPa as PIII treatment time increased. These results indicate nitrogen PIII is very promising in improving optical and mechanical properties of PPHMDSN films.